The G20 development agenda : an Indian perspective - Shome, Parthasarathi, 1950- (Delhi, India : Cambridge University Press, 2015)
"Analyses the evolution and broadening of the G20's agenda from global financial sector matters to covering a vast development agenda"--
Preface -- Introduction -- Group of 20 : the development agenda - an Indian perspective / Parthasarathi Shome, Francis Rathinam -- The development agenda -- Commodity market policy for food security : the road ahead for G20 / Rajesh Chakrabarti, Francis Rathinam, Vijay Varadi -- Recycling global surpluses for infrastructure investment in emerging market economies / Renu Kohli -- G20 : impact of the crisis with special reference to India and international burden sharing / D.K. Srivastava -- India's growth prospect : structural impediment / Kirit S Parikh -- Energy security and environmental sustainability -- The co-benefit principle and the Durban platform : towards an inclusive framework for negotiating climate finance / A. Damodaran -- Greening the G20 agenda : a way forward / Parthasarathi Shome and Amrita Goldar -- Revisiting fossil-fuel subsidies in the context of ongoing G-20 dialogue : a discussion with special reference to India / Meeta Mehra and Divya Datt -- Should India join the international energy agency? / Prodipto Ghosh -- Contributors -- Index.
Includes bibliographical references and index.
Keywords: Economic assistance -- India; Economic development projects -- Management; Economic policy -- International cooperation; India -- Economic conditions -- 21st century; Group of Twenty countries -- Economic policy